2014
DOI: 10.1371/journal.pone.0102781
|View full text |Cite
|
Sign up to set email alerts
|

Primary Health Care Utilization by the Mexican Indigenous Population: The Role of the Seguro Popular in Socially Inequitable Contexts

Abstract: ObjectiveTo analyze the relationship between primary health care utilization and extended health insurance coverage under the Seguro Popular (SP) among Mexican indigenous people.MethodologyA cross-sectional analysis was conducted using data from the Mexican National Nutrition Survey 2012 (n = 194,758). Quasi-experimental matching methods and nonlinear regression probit models were used to estimate the influence of SP on primary health care utilization.Results25% of the Mexican population reported having no hea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
23
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 23 publications
(25 citation statements)
references
References 17 publications
1
23
0
Order By: Relevance
“…First, increasing health insurance ARR and physician density at PHC institutions were associated with more outpatient visits and admissions and more likelihood of visiting PHC institutions. Previous studies have found that introduction of PHC providers would lead to a shift of care from specialists to primary care for disease management in different settings [ 30 – 34 ]. In addition, studies in Sweden and Mexico have indicated that government financial investment in PHCs increased the number of visits to PHCs [ 12 , 35 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…First, increasing health insurance ARR and physician density at PHC institutions were associated with more outpatient visits and admissions and more likelihood of visiting PHC institutions. Previous studies have found that introduction of PHC providers would lead to a shift of care from specialists to primary care for disease management in different settings [ 30 – 34 ]. In addition, studies in Sweden and Mexico have indicated that government financial investment in PHCs increased the number of visits to PHCs [ 12 , 35 ].…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies have found that introduction of PHC providers would lead to a shift of care from specialists to primary care for disease management in different settings [ 30 – 34 ]. In addition, studies in Sweden and Mexico have indicated that government financial investment in PHCs increased the number of visits to PHCs [ 12 , 35 ]. The majority of studies have focused on single policies (e.g.…”
Section: Discussionmentioning
confidence: 99%
“…16,30,31 In addition, studies in Sweden and Mexico have both indicated that government financial investment in PHCs can increase the number of visits to these facilities. 20,21 Second, the positive association between ARR at county hospitals and the probability of visiting those hospitals was stronger in areas with higher physician densities in the county hospitals. This finding has some implications for targeted health insurance improvement and health workforce allocation strategies.…”
Section: Discussionmentioning
confidence: 97%
“…17 While China's most recent health system reform was comprehensive, few studies have systematically quantified the impact of this reform on health care-seeking behaviour. The majority of studies in China and other developing countries have focused on individual health reform policies, such as reform of health insurance 4,5,[18][19][20][21] or investment in health workforce. 15,16 Several studies have assessed the effects of the health reform on health care access from a system-wide perspective; however, what is the relationship between specific health policies and health care-seeking behaviour is not examined.…”
mentioning
confidence: 99%
“…Leyva-Flores et al (2013) found that indigenous Mexicans’ health insurance coverage through the program Seguro Popular 1 rose from 14% in 2006 to 62% in 2012, and that their use of hospital services for childbirth increased from 64% to 76% during the same period. Although these are important health achievements, they have not been enough to close the inequalities between the indigenous and non-indigenous populations; rather, health disparities still persist in stunting, infant mortality, health insurance coverage, and health care utilization (Leyva-Flores, Servan-Mori, Infante-Xibille, Pelcastre-Villafuerte, & Gonzalez, 2014; Servan-Mori et al, 2014).…”
Section: Introductionmentioning
confidence: 99%